Acquisition of permanent residence by temporary foreign workers in Canada: A panel study of labour market outcomes before and after the status transition - Wen Ci; Feng Hou; René Morissette (IZA Journal of Development and Migration, 2018)
Using a unique administrative dataset, this study investigates the employment and earnings trajectories of temporary foreign workers (TFWs) during the years surrounding their acquisition of permanent residence in Canada. If the labour market assimilation of TFWs follows a smooth trajectory in the absence of acquisition of permanent residence, any kinks that occur in employment rates and earnings in or after the year when TFWs become permanent residents might plausibly result from the transition to permanent residence. The main finding of the study is that the labour market outcomes of different groups of TFWs in Canada follow different temporal patterns depending on the TFWs' skill level and work permit type. Gains in labour market outcomes resulting from the acquisition of permanent residence appear to be greater for holders of an open work permit and for live-in caregivers than for highly skilled TFWs.
Keywords: J15; 330; Temporary foreign workers; Status transition; Employment; Earnings; Administrative dataset